2022-LBA-607-ESGO How long do our patients stay fasting? a multicentric prospective survey on the perioperative fasting in 924 Patients conducted by the JAGO study group. (27th October 2022) - Beck, Maximilian Heinz; Balci-Hakimeh, Derya; Scheuerecker, Florian; Wallach, Charlotte; Wißbrock, Hannah; Blohmer, Jens-Uwe; Sehouli, Jalid; Pietzner, Klaus
Abstract : Introduction: The optimization of perioperative fasting is a key step in increasingly established ERAS (extended recovery after surgery) concepts in (gynecologic) surgery. But only little data exists about actually observed fasting intervals before and after surgery in clinical routine. This prospective study of the JAGO (Young Academy of Gynecologic Oncology) and NOGGO e.V. investigates the length of perioperative fasting in a multicentric survey. Methods: In 13 German gynecologic departments the length of pre- and postoperative fasting intervals were recorded by questionnaire. Furthermore, the patients' subjective condition, clinical history and experience and ideas about fasting were documented. Subgroup analyses were performed for benign and malignant indications, as well as for the extent of surgery. Results: A total of 924 patients participated in the study. On average, patients did not eat for 17:02 h and did not drink for 9:21 h before surgery. The first postoperative meal was 9:42 h after surgery. Patients with malignant indications had significantly longer pre- (Δ=67 min) and postoperative (Δ=166 min) fasting intervals. Prolonged fasting intervals were also observed for patients with extensive surgery. In general patients felt well informed and the majority did not feel impaired by the adherence to fasting restrictions. Conclusions: Patients fast significantly longer than recommended. Even more prolonged fasting intervals are observed in patients with malignant indications and extensive surgeries, where optimized fasting could play the greatest role. Therefore, better protocols on optimized perioperative fasting need to be implemented in routine clinical practice.